Development of prestressed unbonded and bonded CFRP strengthening solutions for tensile metallic members. (15th February 2019) - Hosseini, Ardalan; Ghafoori, Elyas; Motavalli, Masoud; Nussbaumer, Alain; Zhao, Xiao-Ling; Al-Mahaidi, Riadh; Terrasi, Giovanni
Highlights: A novel friction-based mechanical clamping system was developed to anchor CFRP plates to steel. No reduction in the ultimate capacity of the system was observed after 10 million fatigue cycles. Performance of the proposed PUR system was experimentally compared to that of the PBR solution. A very good correlation was found between the experimental results and the proposed analytical models. Prestressed NM CFRP reinforcements are much more effective than nonprestressed UHM CFRPs. Abstract: In this study, a novel unbonded mechanical clamping system was developed for the strengthening of tensile metallic members using prestressed carbon fiber reinforced polymer (CFRP) plates. The system clamps a pair of prestressed CFRP reinforcement to a metallic substrate and provides an almost uniform contact pressure over the CFRP plate along the anchorage length. A finite element simulation was used to optimize the design of the mechanical components of the system. Subsequently, a set of static and fatigue tests was performed to evaluate the performance of the optimized design. Experimental results revealed that the proposed mechanical clamping system is capable of transferring the entire tensile capacity of the CFRP plates to the steel substrate, even after experiencing 10 million fatigue cycles. The comparative performance of the developed clamps was further investigated by a set of static tests on steel plate specimens strengthened with the prestressed bonded reinforcement (PBR) and the newly developed prestressed unbonded reinforcement (PUR) systems. Furthermore, simple analytical models are proposed to formulate the stress state in prestressed unbonded and bonded CFRP-strengthened tensile metallic members. The accuracy of the proposed analytical formulations was verified by the experimental results obtained during the current study. Experimental results revealed that the efficacy of having relatively high prestressing forces in the normal modulus (NM) CFRP reinforcements is much higher than the stiffness improvement obtained by using ultra-high modulus (UHM) CFRPs. However, the available capacity of the PBR system before debonding failure is far lower than that of the developed PUR solution.